2011
DOI: 10.1097/prs.0b013e3181fed4f7
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Mouse Model of Cutaneous Radiation Injury

Abstract: This model of cutaneous radiation injury delivers reproducible localized effects, mimicking the injury pattern seen in human subjects. This technique can be used to study radiation-induced injury to evaluate preventative and therapeutic strategies for these clinical issues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
58
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 27 publications
(33 reference statements)
3
58
0
1
Order By: Relevance
“…This mirrors the early transient erythema and a secondary delayed erythema observed in the clinic [53,54]. The opposite has also been reported: blood flow measured by laser Doppler in irradiated hamster parotid gland and mouse skin decreased from baseline up to 2 or 3 weeks [34,55]. Irradiation of hamster cheek pouch muscle also caused microvascular red blood cell velocity to decrease as determined by intravital microscopy [56].…”
Section: Reviewmentioning
confidence: 61%
“…This mirrors the early transient erythema and a secondary delayed erythema observed in the clinic [53,54]. The opposite has also been reported: blood flow measured by laser Doppler in irradiated hamster parotid gland and mouse skin decreased from baseline up to 2 or 3 weeks [34,55]. Irradiation of hamster cheek pouch muscle also caused microvascular red blood cell velocity to decrease as determined by intravital microscopy [56].…”
Section: Reviewmentioning
confidence: 61%
“…(23) The authors reported dermal thickening at 2 weeks post-radiation that progressively increased up to their 6 week end-point. In addition, they also found greater Smad3 expression measured by immunohistochemical staining of irradiated skin specimens, indicating activation of the TGFβ1/Smad pathway that contributes to ECM dysregulation.…”
Section: Discussionmentioning
confidence: 99%
“…(19, 20) Multiple pathways controlling dermal homeostasis become dysregulated, the most studied of which is the transforming growth factor beta 1 (TGFβ1)/Smad pathway. (2123) Immediately following irradiation, an inflammatory response occurs in the skin with cellular recruitment. These inflammatory cells, along with native endothelial cells, fibroblasts, and epidermal cells, begin secreting TGFβ1, which activates Smad signaling intermediates leading to increased production of collagen and other extracellular matrix (ECM) components.…”
Section: Discussionmentioning
confidence: 99%
“…23 Qualitative LDF imaging has also been used to show a decrease in cutaneous perfusion for six weeks following irradiation. 24 The main disadvantage of LDF is that flow velocity is being used as a surrogate marker for perfusion. While this hypothesis often holds true for normal physiology, pathologic processes that may distort tissue architecture can alter the implied relationship between flow velocity and perfusion.…”
Section: Discussionmentioning
confidence: 99%